Pacing of the interventricular septum with His bundle engagement, unlike myocardial pacings of the right ventricle, does not lead to ventricular dyssynchrony, as assessed by ultra-high frequency ECG. (25th November 2020) - Curila, K; Jurak, P; Karch, J; Halamek, J; Prochazkova, R; Stros, P; Plesinger, F; Smisek, R; Waldauf, P; Susankova, M; Herman, D; Osmancik, P; et al.
Abstract: Background: Nonselective pacing of the distal His bundle is practically just another way of right ventricular septal pacing. It leads to the concomitant activation of the His bundle and septal myocytes with unknown impact on ventricular synchrony. Ultra-high frequency ECG (UHF-ECG) is a novel tool for ventricular depolarization imaging. Purpose: To describe ventricular depolarization patterns during nonselective pacing of a ventricular aspect of His bundle and myocardial captures from different locations in the right ventricle by using the UHF-ECG. Methods: Consecutive patients with an indication for permanent pacing due to bradycardia were included. During pacemaker implantation, the pacing lead was temporarily placed in prespecified locations of the right ventricle (mid-septum, anterior, lateral wall, and the para-hisian area of the RV). When pacing from mentioned locations, myocardial activation time under each specific lead (Vd), and ventricular dyssynchrony (e-DYS) indexes were calculated from UHF-ECG maps, for each particular type of pacing. The demonstration of UHF-ECG maps during pacing from different locations of the right ventricle is shown in the figure. Results: Two hundred and fifty UHF ECG recordings were performed in forty-six patients. The calculated mean e-DYS parameter was significantly shorter during non-selective capture of the distal His bundle (14±8 ms) compared to each of myocardial captures of the right ventricle (pure myocardial para-hisian; 35±12 ms, mid-septal; 28±11 ms, anterior wall; 51±16 ms and lateral wall; 62±19 ms (p<0.001). The Vd was also shortest during non-selective capture of the distal His bundle (39±5 ms) compared to each of the others (pure myocardial para-hisian; 52±11 ms, RV mid-septal; 57±11 ms, RV anterior wall; 68±12 ms and RV lateral wall pacing; 85±14 ms (p<0.001). Conclusion: Pacing of the basal interventricular septum with the engagement of the His bundle produced a superior depolarization pattern in both heart ventricles compared to other types of right ventricular myocardial capture, as assessed using UHF-ECG. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Charles University in Prague